The LIver SEntinel LYmph-node (LISELY) study: A prospective intraoperative real time evaluation of liver lymphatic drainage and sentinel lymph-node using near-infrared (NIR) imaging with Indocyanine Green (ICG). Issue 12 (December 2022) - Ruzzenente, Andrea; Conci, Simone; Isa, Giulia; Campagnaro, Tommaso; Pedrazzani, Corrado; De Bellis, Mario; Marchitelli, Ivan; Castelli, Claudia; Pecori, Sara; Guglielmi, Alfredo
Abstract: Near-infrared (NIR) imaging with Indocyanine green (ICG) has been recently proposed for the sentinel lymph node (SLN) and lymphatic out-flow detection in several tumors. Nowadays its application in primary and secondary liver (LCs) and biliary cancers (BTCs) remains uninvestigated. A proof-of-concept prospective observational study including 18 patients underwent surgery for LCs and BTCs from September 2021 to November 2021 was carried out. The intraoperative NIR imaging with ICG was detected at predefined temporary intervals in order to identify the main lymphatic out-flow and the SLN. In 14 patients (77.8%) the lymphatic outflow pathway was visualized with a median time of 3 min after ICG injection (IQR 3–10). The SLN was detected and confirmed at the histological examination in 12 patients (66.7%). Intraoperative NIR imaging with ICG is a safe and feasible method to identify the lymphatic out-flow and SLN in LCs and BTCs.